Content validity of the comprehensive international classification of functioning, disability and health (ICF) core set for low back pain from the perspective of physicians: a Delphi survey. (March 2013) - Glocker, Catherine; Kirchberger, Inge; Gläßel, Andrea; Fincziczki, Agnes; Stucki, Gerold; Cieza, Alarcos
Objectives: The 'Comprehensive ICF Core Set for low back pain (LBP)' is an application of the International Classification of Functioning, Disability and Health (ICF) and represents the typical spectrum of problems in functioning of patients with LBP. The objective of this study was to validate this ICF Core Set from the perspective of physicians. Methods: Physicians experienced in the treatment of LBP were asked about the patients' problems, patients' resources and aspects of environment that physicians take care of in a three-round survey using the Delphi technique. Responses were linked to the ICF. Results: Seventy-one physicians in 36 countries named 707 concepts that covered all ICF components. One hundred ninety-three ICF categories were linked to these answers. Three ICF categories were not represented in the Comprehensive ICF Core Set for LBP although at least 75% of the participants have rated them as important. Twenty-six concepts were linked to the not yet developed ICF component personal factors and 21 issues were not covered by the ICF. Discussion: The high percentage of ICF categories represented in the ICF Core Set for LBP indicates good content validity from the perspective of the physicians. However, some issues were raised that were not covered and need to be investigated further.